Larval development of Holothuria tubulosa, a new tractable system for evo-devo - Perillo, Margherita; Alessandro, Tanya; Toscano, Alfonso; Annunziata, Rossella (Frontiers in Ecology and Evolution, 2024)
To explore animal diversity, new experimentally tractable organisms must be established.Echinoderms include five groups of marine animals that have been used as developmental models for over a century thanks to their low costs, high fecundity, optically clear larvae and genetic tractability. An additional advantage of echinoderms is that their larval forms display diverse morphologies. This rich diversity enables comparative studies to investigate the evolutionary relationships among cell types, tissues, and organs. However, reproducible protocols to obtain gametes, detailed information on embryogenesis, and genomic tools have been optimized only for selected species of sea urchins and sea stars. To address this gap, we established the abundant Mediterranean sea cucumber Holothuria tubulosa as a new experimental system. Here we describe a method to reliably obtain gametes and make embryonic cultures multiple times from the same animal and characterize unique larval tissues combining immunohistochemistry and high-resolution microscopy. This work 2 represents a step forward in our understanding of holothurian development and establishes H. tubulosa as an emerging experimental system for evo-devo and other biological disciplines.